A Novel Signal Restoration Method of Noisy Photoplethysmograms for Uninterrupted Health Monitoring - Aikaterini Vraka; Roberto Zangróniz; Aurelio Quesada; Fernando Hornero; Raúl Alcaraz; José J. Rieta (Sensors, 2023)
Health-tracking from photoplethysmography (PPG) signals is significantly hindered by motion artifacts (MAs). Although many algorithms exist to detect MAs, the corrupted signal often remains unexploited. This work introduces a novel method able to reconstruct noisy PPGs and facilitate uninterrupted health monitoring. The algorithm starts with spectral-based MA detection, followed by signal reconstruction by using the morphological and heart-rate variability information from the clean segments adjacent to noise. The algorithm was tested on (a) 30 noisy PPGs of a maximum 20 s noise duration and (b) 28 originally clean PPGs, after noise addition (2–120 s) (1) with and (2) without cancellation of the corresponding clean segment. Sampling frequency was 250 Hz after resampling. Noise detection was evaluated by means of accuracy, sensitivity, and specificity. For the evaluation of signal reconstruction, the heart-rate (HR) was compared via Pearson correlation (PC) and absolute error (a) between ECGs and reconstructed PPGs and (b) between original and reconstructed PPGs. Bland-Altman (BA) analysis for the differences in HR estimation on original and reconstructed segments of (b) was also performed. Noise detection accuracy was <semantics>90.91%</semantics> for (a) and 99.38–100% for (b). For the PPG reconstruction, HR showed <semantics>99.31%</semantics> correlation in (a) and >90% for all noise lengths in (b). Mean absolute error was <semantics>1.59</semantics> bpm for (a) and 1.26–1.82 bpm for (b). BA analysis indicated that, in most cases, <semantics>90%</semantics> or more of the recordings fall within the confidence interval, regardless of the noise length. Optimal performance is achieved even for signals of noise up to 2 min, allowing for the utilization and further analysis of recordings that would otherwise be discarded. Thereby, the algorithm can be implemented in monitoring devices, assisting in uninterrupted health-tracking.